Discovery and Evaluation of Polymorphisms in the and Promoter Regions for Risk of Korean Lung Cancer - Jae Sook Sung; Kyong Hwa Park; Seung Tae Kim; Yeul Hong Kim (Genomics & Informatics)
AKT is a signal transduction protein that plays a central role in the tumorigenesis. There are 3 mammalian isoforms of this serine/threonine protein kinase-AKT1, AKT2, and AKT3-showing a broad tissue distribution. We first discovered 2 novel polymorphisms (AKT2 -9826 C/G and AKT3 -811 A/G), and we confirmed 6 known polymorphisms (AKT2 -9473 C/T, AKT2 -9151 C/T, AKT2 -9025 C/T, AKT2 -8618G/A, AKT3 -675 A/-, and AKT3 -244 C/T) of the AKT2 and AKT3 promoter region in 24 blood samples of Korean lung cancer patients using direct sequencing. To evaluate the role of AKT2 and AKT3 polymorphisms in the risk of Korean lung cancer, genotypes of the AKT2 and AKT3 polymorphisms (AKT2 -9826 C/G, AKT2 -9473 C/T, AKT2 -9151 C/T, AKT2 -9025 C/T, AKT2 -8618G/A, and AKT3 -675 A/-) were determined in 360 lung cancer patients and 360 normal controls. Statistical analyses revealed that the genotypes and haplotypes in the AKT2 and AKT3 promoter regions were not significantly associated with the risk of lung cancer in the Korean population. These results suggest that polymorphisms of the AKT2 and AKT3 promoter regions do not contribute to the genetic susceptibility to lung cancer in the Korean population.